Code Switching Types Used by the English Teacher in English Classroom at SMA 1 Malili - Rahmawati Upa (Ethical Lingua: Journal of Language Teaching and Literature, 2014)
This research aimed at finding out: (1) the types of code switching used by the English teacher (2) the dominant types of code switching used by the teacher and (3) the teacher’s perceptions toward the use of teachers’ code switching in English classroom at SMA I Malili. This research took one of the English teachers as the subject of the research and the data were gathered through observation, interview, and recorded by using video recorder and field notes. The data were then analyzed using discourse analysis. The result of analysis showed that (1) the teacher used three types of code switching, namely: intrasentential code switching, inter-sentential code switching, and tag switching; (2) the dominant types of code switching used was intrasentential code switching followed by inter sentential code switching and tag switching (3) the interviewed teacher responded positively toward the use of code switching by the English teacher in English classroom.